Enhanced Field Emission properties of Carbon Nanotube films using densification technique - Lim, Yu Dian (2021)
It has been reported that Carbon Nanotubes (CNTs) films show much lower Field Emission (FE) current density than single CNT, due to the screening effect between CNTs. To minimize the screening effect, a widely-reported technique is to grow CNTs in isolated islands to form CNT arrays, which requires precise photolithography technique and CNT growth control. In this study, we demonstrate a simpler alternative to reduce the screening effect in CNT films using ethanol-densification. To perform densification, ethanol is dripped onto CNT films and dried in ambient condition to form CNT clusters. Densified CNT films show 2–4 times improvement in FE current density. This improvement in current density can be attributed to the enhanced localized electric field on CNT tips, as suggested by the simulation results. From the repeated densification and FE measurements, it is found that densified CNT films achieved consistent current density of 9 ∼ 11 mA/cm2. At the same time, densified CNT film exhibits good FE current stability over prolonged continuous emission, with slight degradation from ∼10 to ∼9.64 mA/cm2 over 4000 s continuous emission.